2021
DOI: 10.1080/10937404.2021.1975182
|View full text |Cite
|
Sign up to set email alerts
|

A review of the toxicology of oil in vertebrates: what we have learned following the Deepwater Horizon oil spill

Abstract: In the wake of the Deepwater Horizon (DWH) oil spill, a number of government agencies, academic institutions, consultants, and nonprofit organizations conducted lab-and field-based research to understand the toxic effects of the oil. Lab testing was performed with a variety of fish, birds, turtles, and vertebrate cell lines (as well as invertebrates); field biologists conducted observations on fish, birds, turtles, and marine mammals; and epidemiologists carried out observational studies in humans. Eight years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 179 publications
(228 reference statements)
0
18
0
2
Order By: Relevance
“…In line with the basic definition, oil is an organic compound that is soluble or readily soluble in water but not readily soluble in other liquids and is found in crude oil. An oil spill occurs when oil floats on the surface of bodies of water and is carried by the wind, currents, and tides [1][2][3][4][5].…”
Section: What Is Meant By An Oil Spill?mentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the basic definition, oil is an organic compound that is soluble or readily soluble in water but not readily soluble in other liquids and is found in crude oil. An oil spill occurs when oil floats on the surface of bodies of water and is carried by the wind, currents, and tides [1][2][3][4][5].…”
Section: What Is Meant By An Oil Spill?mentioning
confidence: 99%
“…Even without the aid of wind and water currents, the oil will spread if its surface tension is low. Oil is more likely to spread in warmer waters than in extremely cold ones since increased temperatures can reduce a liquid's surface tension [1][2][3][4][5][6][7][8][11][12][13][14][15].…”
Section: Oil Spill Behavior In Marine Environmentsmentioning
confidence: 99%
“…Turtles, shellfish, fish, algae, among other organisms were found with remnants of the oil and many fishermen/women reported the decrease of shellfish and fish in the affected regions. Environmental exposure to oil can trigger physiological changes that depend on the duration and geographic scale of exposure, the habitat diversity of the affected site, and increased sublethal effects [1,7,[34][35][36]. Thus, these effects may be even more intense with the new traces of oil on the Brazilian coast, demonstrating that the problem is still active in these territories.…”
Section: Oil Spill In Artisanal Fishing Communities: Environmental Co...mentioning
confidence: 99%
“…Studies warn about the possibility of environmental imbalance in locus, and also in regions relatively distant from the main point of contamination, which increases the attention in areas more sensitive to changes, such as mangrove regions. Benthic and mangrove regions are environments that are more susceptible to impacts, through the sedimentation of this material in coastal micro and macrofauna, amplifying along the chain the toxicity, genetic alterations, and other damages of the contamination [36,37]. Although toxicological tests conducted in the Baixo Jaguaribe region in the state of Ceará indicated non-significant damage to the genetic material of shellfish due to the influence of oil pollutants [38], a recent study pointed out the relationship between exposure from the 2019 oil spill and decreased growth rate of a type of microalgae of the zooxanthella species Symbiodinium glynnii, mutualistically influencing the maintenance of corals, which may undergo bleaching processes [39].…”
Section: Oil Spill In Artisanal Fishing Communities: Environmental Co...mentioning
confidence: 99%
“…Research on the effects of oil on marine fishes has expanded following the Deepwater Horizon oil spill in the Gulf of Mexico in 2010. Laboratory studies after the blowout identified adverse effects of petroleum exposure, including reduced growth, impaired reproduction, and increased incidence of death and disease in several fish species (Beyer et al, 2016; Grosell & Pasparakis, 2021; McGruer et al, 2019; Murawski et al, 2021; Pasparakis et al, 2016; Takeshita et al, 2021). Early life stages of fish are known to be particularly vulnerable because the fish inhabit the upper water column and are undergoing critical developmental stages (Incardona et al, 2014; McGruer et al, 2019; Pasparakis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%